A New Method for Dual Fully Fuzzy Linear Systems by use LU Factorizations of the Coefficient Matrix - Mashadi Mashadi (Institut Teknologi Bandung, 2010)
In this paper we will discuss an alternative way to solve dual fully fuzzy linear system of the form . Next we crisp coefficient matrix Â and Â through form LU factorizations and we will construct a simple algorithm for the solution of these system. Finally we will illustrate our method by solving some examples.